Evaluation of concordance among three cardiac output measurement techniques in adult patients during cardiovascular surgery postoperative care (2017)
Introduction: The standard method for cardiac output measuring is thermodilution although it is an invasive technique. Transesophageal Echocardiography (TEE) offers a dynamic and functional alternative to thermodilution. Objective: Analyze concordance between two TEE methods and thermodilution for cardiac output assessment. Methods: Observational concordance study in cardiovascular surgery patients that required pulmonary artery catheter. TEE cardiac output measurement at both mitral annulus (MA) and left ventricle outflow tract (LVOT) were performed. Results were compared with thermodilution. Correlation was evaluated by Lin’s concordance correlation coefficient and Bland---Altman analysis. Statistical analysis was undertaken in STATA 13.0.Results: Twenty-five patients were enrolled. Fifty two percent of patients were male, median age and ejection fraction was 63 years and 35% respectively. Median thermodilution, LVOT and MA -measured cardiac output was 3.25 L/min, 3.46 L/min and 8.4 L/min respectively. Different values between thermodilution and MA measurements were found (Lin concordance = 0.071; Confidence Interval 95% = −0.009 to 0.151; Spearman’s correlation = 0.22) as values between thermodilution and LVOT (Lin concordance = 0.232; Confidence Interval 95% = −0.12 a 0.537; Spearman’s correlation 0.28). Bland---Altman analysis showed greater difference between MA measurements and thermodilution (DM = −0.408; Bland---Altman Limits = −0.809 to −0.007), than the other echocardiographic findings (DM = 0.007; Bland---Altman Limits = −0.441 to 0.428). Conclusion: Results from cardiac output measurement by doppler and 2D-TEE on both MA and LVOT do not correlate with those obtained by thermodilution.